2015
DOI: 10.1039/c4cc08004a
|View full text |Cite
|
Sign up to set email alerts
|

Self-catalysis by aminosilanes and strong surface oxidation by O2 plasma in plasma-enhanced atomic layer deposition of high-quality SiO2

Abstract: Plasma-enhanced atomic layer deposition (PE-ALD) has been applied to prepare high-quality ultrathin films for microelectronics, catalysis, and energy applications. The possible pathways for SiO2 PE-ALD using aminosilanes and O2 plasma have been investigated by density functional theory calculations. The silane half-reaction between SiH4 and surface -OH is very difficult and requires a high activation free energy of 57.8 kcal mol(-1). The introduction of an aminosilane, such as BDMAS, can reduce the activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…Recently, quantum chemistry (QC), in particular density functional theory (DFT) calculations, has become a powerful tool to explicit the ALD chemistry at an atomic scale. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Dey et al 31 investigated the transmetalation reactions in Cu ALD using diethylzinc as the reducing agent, following experiments by Lee et al 8 Lin et al 32 have investigated the competition between ligand-exchange reactions and surface decomposition of Cu(acac) 2 on a Si(100)-2 Â 1 surface. More recently, we have studied the surface reactions of ( n Bu 3 P) 2 Cu(acac) and Cu(acac) 2 precursors on a Ta(110) surface.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, quantum chemistry (QC), in particular density functional theory (DFT) calculations, has become a powerful tool to explicit the ALD chemistry at an atomic scale. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Dey et al 31 investigated the transmetalation reactions in Cu ALD using diethylzinc as the reducing agent, following experiments by Lee et al 8 Lin et al 32 have investigated the competition between ligand-exchange reactions and surface decomposition of Cu(acac) 2 on a Si(100)-2 Â 1 surface. More recently, we have studied the surface reactions of ( n Bu 3 P) 2 Cu(acac) and Cu(acac) 2 precursors on a Ta(110) surface.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is mainly that H 2 O can form hydrogen bonding interactions through H 2 O…H 2 O bonds and lower the activation energy of Si-O bond formation and Cl elimination via a six-member ring (6MR) transition state, H 2 O-assisted-TS1 B1 , shown in Figure 4 . The accelerated half-reaction via the hydrogen bonding interaction of H 2 O…H 2 O may be termed as H 2 O-assisted hydrolysis, which is similar to Lewis-base catalysis in SiO 2 ALD through the OH…N hydrogen bond [ 14 , 23 , 24 ]. As a matter of fact, there are H 2 O-assisted reactions in nature, such as hydrolysis or solvolysis [ 25 - 28 ], tautomerization or proton transfer [ 29 - 34 ], decomposition [ 35 - 37 ], and catalysis [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…With the high energy species, the PEALD, which can enhance the reactivity at low temperatures, is suitable for the temperaturesensitive deposition process. Now PEALD has been applied to prepare high-quality ultrathin films for microelectronics, catalysis, and new energy applications [217,218]. Lee et al [219] reported a low frequency plasma assisted ALD technique to deposit Al x O y layer on polyethylene naphthalate substrates as barrier layer.…”
Section: Inorganic Thin Film Depositionmentioning
confidence: 99%